Tachinid Fly (Diptera: Tachinidae) Parasitoids of Danaus plexippus (Lepidoptera: Nymphalidae). (10th July 2017) - Oberhauser, Karen; Elmquist, Dane; Perilla-López, Juan Manuel; Gebhard, Ilse; Lukens, Laura; Stireman, John
Abstract: Extensive rearing of monarch larvae ( Danaus plexippus L.) through the citizen science Monarch Larva Monitoring Project (MLMP) revealed that monarchs' primary parasitoids are flies in the family Tachinidae and that these parasitoids result in appreciable larval mortality. We document the tachinid community that attacks monarchs in the United States, evaluate their relative frequency, and examine variation in their specificity, oviposition strategy, and use of host stages. Based on results of rearing >20, 000 monarchs by MLMP volunteers, overall parasitism by tachinids across life stages was 9.8% (17% for monarchs collected as fifth instars). We identified the flies that emerged from 466 monarch hosts, and found seven Tachinidae species. In decreasing order of frequency, these included Lespesia archippivora (Riley), Hyphantrophaga virilis (Aldrich & Webber), Compsilura concinnata (Meigen), Leschenaultia n. sp., Madremyia saundersii (Williston), Lespesia sp., and Nilea erecta (Coquillett) . Lespesia sp., Leschenaultia n. sp., and N. erecta had not been previously reported as monarch parasitoids, and Leschenaultia n. sp. is apparently undescribed. We include new state records (Texas and Iowa) for C. concinnata . Lespesia archippivora and C. concinnata were overrepresented as parasitoids of later instars and were absent from monarchs collected as eggs, but H. virilis and Leschenaultia sp., which lay their eggs on foliage, were reared from caterpillars collected as eggs. To our knowledge, we include the first report of multiparasitism of monarchs, in which more than one parasitoid species emerged from a host. The biology of the tachinid parasitoids we identified and their relationship with monarchs is examined. Resumen La cría extensiva de orugas de mariposas monarca ( Danaus plexippus L.) con el apoyo del programa de ciencia ciudadana Monarch Larva Monitoring Project (MLMP), reveló que los parasitoides primarios de las mariposas monarca son moscas de la familia Tachinidae y que estos parasitoides son responsables de una considerable mortalidad de orugas. Se documenta la comunidad de tachínidos que atacan mariposas monarca en los Estados Unidos, se evalúa su frecuencia relativa y examina su variación especifica, estrategia de oviposición y uso de los estadios del hospedante. Basados en los resultados de la cría de más de 20.000 mariposas monarca por parte de voluntarios del MLMP, se encontró un total de 9.8% de parasitoidismo durante los diferentes estadios (17% durante el quinto instar). Se identificaron tachínidos emergidos de 466 orugas, encontrándose siete especies de Tachinidae. En orden decreciente de frecuencia se encontró: Lespesia archippivora (Riley), Hyphantrophaga virilis (Aldrich & Webber), Compsilura concinnata (Meigen), Leschenaultia n. sp., Madremyia saundersii (Williston), Lespesia sp., y Nilea erecta (Coquillett). Lespesia sp., Leschenaultia n. sp. y N. erecta son reportadas por primera vez como parasitoides de larvas de mariposas monarca, Leschenaultia n. sp. presentó un rango amplio de distribución. Se presentan nuevos registros de C. concinnata para Texas y Iowa. Lespesia archippivora y C. conninnata fueron las especies que más se encontraron parasitando instares tardíos y no se encontraron en monarcas recolectadas desde huevo, en cambio, las que depositan micro-huevos H. virilis y Leschenaultia sp. sobre el follaje, fueron criadas de orugas recolectadas en estado de huevo, en las frecuencias altas esperadas. Hasta donde sabemos se presenta el primer reporte de multiparasitismo en mariposas monarca, con mas de una especie de parasitoide emergiendo de un hospedante. El multiparasitismo ocurrió en las tres especies de parasitoides más abundantes en frecuencias bajas. Se examina la biología de las especies de tachínidos encontradas y su relación con las mariposas monarca.